Penyediaan Tempat Pembuangan Sampah dan Edukasi Klasifikasi Jenis – Jenis Sampah - Koh, Viennie; Jeffrey, Jeffrey; Wilhelmina, Wilhelmina; Trisca, Vivian; Afrianty, Shintya; Lita, Lita; Danat, Vandryana; Lionardo, Lionardo; Kevin, Valerianus; Christhomas, Jacky (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
SEPORA is a form of community empowerment where we help local people to create a cleaner and healthier environment by providing public rubbish bins with logo to differentiate between organic and inorganic waste types. This activity uses a qualitative descriptive approach with direct observation to the location of Kabil. The observation result of the Kabil region is a fairly dense residential area. Not all residents of RW 016 have a place for their daily waste disposal. The output of this activity is providing eight units of garbage bins in the Kabil area and socialization on the procedures for grouping types of organic and inorganic waste. This activity aims to increase public awareness toward the importance level of clean and healthy living.